THE ROMANTICISM OF MUSTFA ZAIDI - Farida Usman; Dr. Robina Shaheen (Zaban-o-Adab, 2022)
In Urdu literature, the effects of romantic trends are found in one form or another, especially against the objectivism of the Aligarh movement, this movement gave energy to many trends in literature, both in prose and poetry, and creators made use of it. The literature that developed under the influence of the progressive movement emphasizes the Marxist point of view, the writers associated with this movement either accepted it willingly or made certain aspects of its manifesto strongly the subject of their creation. After Faiz Ahmed Faiz in poetry, Mustafa Zaidi, despite being influenced by the progressive manifesto, adopted romantic aspects. In his poetry, the effects of romanticism are mixed, love, grief, retrospect, deviation from traditions, imagination, from the present. Elements such as escape are present in Zaidi’s poetry. Through this article, an attempt has been made to bring out the main romantic tendencies in Mustafa Zaidi’s poetry (ghazels and verse).